Health-related quality of life following minimally invasive totally endoscopic mitral valve surgery - Huang, Ling-chen (J Cardiothorac Surg, 2020)
BACKGROUND: To compare the impact of two different types of mitral valve surgery on health-related quality of life, we conducted a retrospective study comparing modified totally endoscopic mitral valve surgery with median sternotomy mitral valve surgery. METHODS: A total of 163 patients who underwent mitral valve surgery at our institution between January 1, 2019 and December 31, 2019 were enrolled. For these 163 patients, mitral valve surgery was performed using either a modified totally endoscopic approach or median sternotomy approach. We used the numerical rating scale and the Scar Cosmesis Assessment and Rating Scale to measure pain intensity and the aesthetic appearance of the surgical incision and used the MOS 36-item Short-Form Health Survey to assess health-related quality of life. RESULTS: Seventy-eight patients underwent the modified totally endoscopic mitral valve surgery, and eighty-five patients underwent the median sternotomy mitral valve surgery. The two groups of patients were similar in terms of demographics and echocardiography findings. The number of bioprosthetic valve replacements performed was significantly higher in the totally endoscopic group than in the median sternotomy group (p = 0.04), whereas the subvalvular apparatus was less preserved in only 33 cases in the totally endoscopic group (p = 0.01). The rate of postoperative adverse events was similar between the two groups. The pain was mild and aesthetic appearance was significantly better in the totally endoscopic approach group than in the sternotomy approach group. Significant differences in the scores for the bodily pain and mental health subscales of the MOS 36-item Short-Form Health Survey were found between the two groups. CONCLUSIONS: Compared with median sternotomy mitral valve surgery, totally endoscopic mitral valve surgery has an equally good treatment effect, improving patient’s health-related quality of life with a better cosmetic appearance and a lower pain intensity. Our study suggested that the totally endoscopic approach is superior to the median sternotomy approach in terms of pain intensity, aesthetic appearance and health-related quality of life.